Efficacy Evaluation of Neurofeedback-Based Anxiety Relief - Chen, Chao; Xiao, Xiaolin; Belkacem, Abdelkader Nasreddine; Lu, Lin; Wang, Xin; Yi, Weibo; Li, Penghai; Wang, Changming; Sha, Sha; Zhao, Xixi; Ming, Dong (Frontiers in Neuroscience, 2021)
Anxiety disorder is a mental illness that invloves extreme fear or worry, which can alter the balance of chemicals in the brain. This change and evaluation of anxiety state are accompanied by a comprehensive treatment procedure. It is well-known that the treatment of anxiety is chiefly based on psychotherapy and drug therapy, and there is no objective standard evaluation. In this paper, the proposed method focuses on examining neural changes to explore the effect of mindfulness regulation in accordance with neurofeedback in patients with anxiety. We designed a closed neurofeedback experiment that includes three stages to adjust the psychological state of the subjects. A total of 34 subjects, 17 with anxiety disorder and 17 healthy, participated in this experiment. Through the three stages of the experiment, electroencephalography(EEG) resting state signal and mindfulness- based EEG signal were recorded. Power spectral density was selected as the evaluation index through the regulation of neurofeedback mindfulness, and repeated analysis of variance (ANOVA) method was used for statistical analysis. The findings of this study reveal that the proposed method has a positive effect on both types of subjects. After mindfulness adjustment, the power map exhibited an upward trend. The increase in the average power of gamma wave indicates the relief of anxiety. The enhancement of the wave power represents an improvement in the subjects' mindfulness ability. At the same time, the results of ANOVA showed that p< 0.05,i.e., the difference was significant. From the aspect of neurophysiological signals, we objectively evaluated the ability of our experiment to relieve anxiety. The neurofeedback mindfulness regulation can effect on the brain activity pattern of Anxiety disorder patients.